Influence of power source type on time dependence of the plasma parameters of a pulse discharge with a hollow cathode - Bazhenov, V.Yu.; Tsiolko, V.V.; Piun, V.M. (Problems of Atomic Science and Technology, 2022)
Peculiarities of the time dependence of the plasma parameters of a pulsed discharge with a hollow cathode in low-pressure argon were experimentally determined when using two types of pulsed high-voltage power sources – voltage and current sources (pulse duration up to 10 ms, voltage up to 10 kV). It is shown that the use of pulsed current sources provides significantly more stable discharge glow in the working range of argon pressure variations (2.5…10)·10⁻⁴ Torr. At the same time, the temperature of plasma electrons of the discharge which was powered by a voltage source, was several times higher and could reach 40 eV. Експериментально знайдено особливості часових залежностей параметрів плазми імпульсного розряду з порожнистим катодом у аргоні низького тиску при використанні двох типів імпульсних високовольтних джерел живлення – джерел напруги та струму (тривалість імпульсів до 10 мс, напруга до 10 кВ). Показано, що використання імпульсних джерел струму забезпечує значно більш стабільне горіння розряду в робочому діапазоні змін тиску аргону (2.5…10)·10⁻⁴ Торp. У той же час температура електронів плазми розряду, який живився джерелом напруги, була в кілька разів більшою і могла сягати 40 еВ.